Potential importance of the ear as a post‐anthesis carbon source to improve drought tolerance in spring wheat (Triticum aestivum L.). (26th August 2021) - Kashiwagi, Junichi; Yoshioka, Yuichiro; Nakayama, Suzu; Inoue, Yoshiko; An, Ping; Nakashima, Taiken
Abstract: It is important to explore and propose a potential source for further improvements in drought tolerance in spring wheat ( Triticum aestivum L.). The present study aimed to evaluate the significance of ear as a post‐anthesis carbon source under drought conditions in wheat genotypes with different sink–source balances. Field trials were conducted in 2017 and 2018 for four spring wheat genotypes ( T. aestivum L.) with different sink–source balances in two different soil water conditions, irrigated and drought. The relative importance of a post‐anthesis carbon gain and dry matter remobilization as source functions for grain filling was evaluated in both environments. Digital infrared thermal imagery analysis was undertaken to analyse the contribution of the photosynthetic source to the leaf canopy and ear parts. In irrigated conditions, carbon assimilation was the major source for grain filling in all genotypes, whereas the contribution of dry matter remobilization was up to 20%. This was supported by a larger leaf area index (LAI) with a lower canopy temperature as the soil water stress alleviated. The ear temperature was always maintained below the canopy temperature, irrespective of irrigation treatment. When the drought intensity became more severe, very small leaf area was insufficient as the photosynthetic source organ for grain filling. Under severe drought condition, especially for genotypes with a larger sink capacity, carbon supply from ear itself appeared to play a significant role in grain filling. This study suggested that enhancing ear photosynthesis could be potential target for improving drought tolerance for high‐yielding modern wheat genotypes with larger sink and smaller biomass.